2019
DOI: 10.21776/ub.jpacr.2019.008.03.496
|View full text |Cite
|
Sign up to set email alerts
|

Garcinia Mangostana Peel Extract as Sustainable Fuel Source on Ceria Synthesis under Hydrothermal Condition

Abstract: Cerium (IV) oxide or ceria (CeO2) was fabricated by heating an aqueous extract of Garcinia mangostana and cerium (III) nitrate in hydrothermal autoclave reactor at 200 °C for 3 hours, followed by calcination at 600 °C for 5 hours. The powder X-ray diffraction (XRD) pattern of the precipitate from cerium(III) nitrate under hydrothermal reaction conditions shows no clear XRD peaks, indicating its amorphous nature. In contrast, the products from the calcinated samples exhibit XRD peaks, which correspond to cubic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
(19 reference statements)
0
1
0
Order By: Relevance
“…However, fairly uniform spherical shapes were observed in the Fardood and Ramazani study using black tea extract to synthesis CuO NPs calcinated at 600 °C [ 45 ]. The agglomeration of synthesized CuO NPs at 600 °C might be due to the removal of carbonized materials [ 86 ] which is supported by the Fardood and Ramazani study using coffee powder extract to synthesize CuO NPs [ 13 ]. Thus, the SEM images revealed that the coarsening and coalescence occurred due to the changes in calcination temperature and resulted in NP morphology alteration [ 23 , 83 ].…”
Section: Resultsmentioning
confidence: 96%
“…However, fairly uniform spherical shapes were observed in the Fardood and Ramazani study using black tea extract to synthesis CuO NPs calcinated at 600 °C [ 45 ]. The agglomeration of synthesized CuO NPs at 600 °C might be due to the removal of carbonized materials [ 86 ] which is supported by the Fardood and Ramazani study using coffee powder extract to synthesize CuO NPs [ 13 ]. Thus, the SEM images revealed that the coarsening and coalescence occurred due to the changes in calcination temperature and resulted in NP morphology alteration [ 23 , 83 ].…”
Section: Resultsmentioning
confidence: 96%